2009
DOI: 10.1109/tvcg.2009.182
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Analysis of Sensor Logs using Growth Ring Maps

Abstract: Spatiotemporal analysis of sensor logs is a challenging research field due to three facts: a) traditional two-dimensional maps do not support multiple events to occur at the same spatial location, b) three-dimensional solutions introduce ambiguity and are hard to navigate, and c) map distortions to solve the overlap problem are unfamiliar to most users. This paper introduces a novel approach to represent spatial data changing over time by plotting a number of non-overlapping pixels, close to the sensor positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…We use the visualization technique Growth Ring Map (Bak et al 2009). According to our classification (Table 2), this is a method in which spatial positions are represented by positions on a map and temporal positions by retinal properties.…”
Section: Investigating the Spatio-temporal Distribution Of Photosmentioning
confidence: 99%
“…We use the visualization technique Growth Ring Map (Bak et al 2009). According to our classification (Table 2), this is a method in which spatial positions are represented by positions on a map and temporal positions by retinal properties.…”
Section: Investigating the Spatio-temporal Distribution Of Photosmentioning
confidence: 99%
“…Some researchers use growth ring maps (Bak, 2009) and flower diagram maps (Andrienko, 2013b) to support the investigation of cyclic temporal patterns of event occurrences in different places, which are similar to the approaches used in our work. However, the techniques above are only efficient at extracting the relations of some events that consist of the attributes of movement; the spatial and temporal semantics of movements are not always considered, especially when the requirements of the analyst changes.…”
Section: Movement Events Extractedmentioning
confidence: 99%
“…Growth ring maps (Bak, 2009) and flower diagram maps (Andrienko, 2013b) can also present the relations in different geometries.…”
Section: Relations and Visualizationmentioning
confidence: 99%
“…A comprehensive more recent reference is provided in [5]. Examples of recent significant research in the area of visual analytics can be found in document analysis [14], financial analysis [15], [16] and geo-spatial object analysis [17]. In [18] pioneering work is reported where visual analytics is applied to the field of data mining.…”
Section: Related Workmentioning
confidence: 99%